Ventricular mechanics in patients with aortic valve disease: longitudinal, radial, and circumferential components. (7th February 2013) - Leonardi, Benedetta; Margossian, Renee; Sanders, Stephen P.; Chinali, Marcello; Colan, Steven D.
Abstract: Background: Reduced long-axis shortening despite enhanced global function has been reported in aortic stenosis. We sought to improve the understanding of this phenomenon using multi-dimensional strain analysis in conjunction with the evaluation of left ventricular rotation and twist – ventricular torsion – using tissue Doppler techniques. Methods: A total of 57 patients with variable severity of aortic stenosis, aortic regurgitation, or mixed aortic valve disease, subdivided into six groups, were studied. Ventricular morphology was assessed using long-axis/short-axis and mass/volume ratios, afterload using end-systolic meridional wall stress, and global performance using ejection fraction. The circumferential and longitudinal strain was measured from two-dimensional images, and left ventricular rotation and twist were estimated as the difference in rotation between the base and apex of the ventricle. Results: Aortic stenosis was associated with higher mass/volume, ejection fraction, circumferential strain and left ventricular rotation and twist, significantly lower end-systolic wall stress, and a trend towards lower longitudinal strain compared with normal. Myocardial mechanics in aortic regurgitation were normal despite ventricular dilation. Mixed aortic valve disease showed findings similar to aortic stenosis. Left ventricular rotation and twist correlated with midwall circumferential strain (r = 0.62 and p < 0.0001), endocardial circumferential strain (r = 0.61 and p < 0.0001), and end-systolic wall stress (r = 0.48 and p < 0.0001), but not with longitudinal strain (r = 0.18 and p > 0.05). Conclusions: Myocardial mechanics are normal in patients with aortic regurgitation, independent of abnormalities in cardiac geometry. Conversely, in aortic stenosis and mixed aortic valve disease, significant alterations in the patterns of fibre shortening are found. The effects of stenosis on cardiac function seem to dominate the effect of ventricular remodelling.